Non-Heart-Beating Donor Heart Transplantation: Breaking the Taboo - Fatullayev, Javid (Med Sci Monit Basic Res, 2015)
Roughly 60% of hearts offered for transplantation are rejected because of organ dysfunction. Moreover, hearts from circulatory-dead patients have long been thought to be non-amenable for transplantation, unlike other organs. However, tentative surgical attempts inspired by the knowledge obtained from preclinical research to recover those hearts have been performed, finally culminating in clinically successful transplants. In this review we sought to address the major concerns in non-heart-beating donor heart transplantation and highlight recently introduced developments to overcome them.